PELATIHAN ACADEMIC WRITING MELALUI PEMANFAATAN TEKNOLOGI ARTIFICIAL INTELLIGENCE (AI) - Naufal, Muhammad Ammar; Pratiwi, Andi Citra; Dassa, Awi; Ihsan, Hisyam; Azis, Andi Asmawati; Fridayanti, Novia (Ininnawa : Jurnal Pengabdian Masyarakat, 2025)
Academic writing is one of the essential skills that university students must acquire, especially in preparation for the IELTS writing test, which demands not only English language proficiency but also logical and systematic thinking skills. Although this skill is crucial, the majority of students in the Faculty of Mathematics and Natural Sciences (FMIPA) at Universitas Negeri Makassar (UNM) still demonstrate limited competence in academic writing, particularly for IELTS purposes. One strategic effort to enhance this skill is through a student mentoring program supported by the FMIPA International Students Community (FISCO), a group comprising students and alumni. This community serves as mentors and teaching assistants in the English for Subject Matter (ESM) program, which specifically guides students in the International Class Program (ICP) in mastering academic skills, with a focus on academic writing as a key component of the IELTS test. Although the mentors generally possess strong academic backgrounds, many of them still face challenges in effectively teaching academic writing techniques. Therefore, this community service activity aims to improve the academic writing skills of ICP mentors through the utilization of Artificial Intelligence (AI) technology. The program was carried out in three main stages: (1) presentation of the material, (2) practical application of AI tools, and (3) interactive discussion. Evaluation results based on questionnaires distributed at the end of the training session indicated that all participants responded positively to the training and showed increased knowledge regarding key aspects of academic writing for IELTS Writing Task 1 and Task 2.